“Gamificación e innovación pedagógica” - Romero Aimacaña, Jhon Alexander (2023)
The current educational process requires significant and transforming changes as the use of gamification and pedagogical innovation, to provide quality and warm teaching experiences to students. This research aims to determine the advantages of gamification and pedagogical innovation for the development of the PEA in seventh grade parallel "A" of General Basic Education, of the Educational Unit "Vicente León" located in Juan Montalvo parish, in the neighborhood La Cocha of Latacunga canton, province of Cotopaxi during the school year 2022-2023. The methodology applied within the research project was based on the interpretative approach that allowed the analysis of the phenomenon in its natural context and determined the real problem. Additionally, we used the qualitative approach with the interview technique and its guide as the instrument and the quantitative approach with the survey technique and its questionnaire instrument. The method applied was deductive and inductive because the premises were analyzed using logic and study, which made it possible to understand the phenomenon. The findings revealed that the PEA continues to employ boring procedures, lacks gamification and pedagogical innovation, and the teacher doesn't incorporate engaging features, which leads to students losing interest and failing to learn. This initiative helps instructors and students by researching cutting-edge educational techniques being used in virtual settings globally to enhance the educational process.